On Some Properties of Orthogonal Polynomials over an Area in Domains of the Complex Plane. II - Abdullayev, F. G. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We investigate polynomials that are orthonormal with weight over the area of a domain with quasiconformal boundary. We obtain new exact estimates for the growth rate of these polynomials.